Synthesis of fatty acid from locally isolated marine algae, Chaetocerosaffinis - Mohammad Anuar, Mohammad Fuad; Mohammad Noor, Normawaty; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (2012)
Several marine diatoms have been known for their high lipid content. Chaetocerosis probably the largest genus of marine planktonic diatoms witn approximately 400 species described. Lipid is important as primary storage for nutrient and essential for cell's growth and function. Nowadays, there are increasing in demands for alternative source of fuel and several attempts have been conducted to find-the best ways for fatty acid collection and algae have been listed as potential sources for lipid. This study was aimed to analyze the production of fatty acids from a common marine algae, chaetoceros affinis during exponential phase, stationary phase and death growth phase. The results showed that saturated fatty acid (SAFA) (46%) and monosaturated fatty acids (MUFA)(15%) have been detected during the all growth phases except for polyunsaturated fatty acids (PUFA). Myristic acid is the major compound found in every phases studied with the highest percentage of 24% at death-gowth phase followed by, palmitic acid with the percentage of 21% and palmitoleic acid covered about 16%.